Methionine Supplementation of Low-Protein Broiler Diets: Influence upon Growth Performance and Efficiency of Protein Utilization - Khajali, Fariborz; Moghaddam, Hasan Nasiri (International Journal of Poultry Science, 2006)
One experiments was conducted to determine the effect of a low-protein diet supplemented with DL- methionine on the growth performance, carcass and litter characteristics of male broilers during the starting (1 to 21d) and growing (22 to 42d) periods. Three levels of DL- methionine (50, 75 and 100% of the level commonly used in commercial broiler diets) were added to the control (22 and 19.4 % CP in the starting and growing periods, respectively) or a low protein diet (19.1 and 16.4% CP in the starting and growing periods, respectively). For those broilers received the control diet, there was no significant effect of methionine level on body weight gain and FCR. For the broilers received the low protein diet, however, those fed the diet with the lowest methionine level had lower feed intake which brought about better FCR (P < 0.05). Final body weight was not significantly affected by diet composition. Breast meat yield was improved by increasing methionine level (P< 0.05). Nitrogen content of the litter was reduced roughly 10% by each percentage unit reduction in dietary CP content, but was not influenced by methionine supplementation.